2019
DOI: 10.1186/s12931-019-1176-x
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling regulates trans-differentiation of stem cell like type 2 alveolar epithelial cells to type 1 epithelial cells

Abstract: Background Type 2 alveolar epithelial cells (AT2s) behave as stem cells and show clonal proliferation upon alveolar injury followed by trans-differentiation (TD) into Type 1 alveolar epithelial cells (AT1s). In the present study we identified signaling pathways involved in the physiological AT2-to-AT1 TD process. Methods AT2 cells can be isolated from human lungs and cultured in vitro where they undergo TD into AT1s. In the present study we identified signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…Proliferation markers like proliferation marker protein 67 ( Mki67 ), forkhead box protein M1 ( Foxm1 ), and polo-like kinase 1 ( Plk1 , Figure 9E) confirmed this general lack of proliferation in epithelial cells as all three were expressed at lower levels in a dose-dependent manner after exposure to nylon fibers. Expression of genes for signaling molecules essential for epithelial growth and development were impressively and dose-dependently downregulated by nylon exposure as well (Figure 9F), including Notch1 and Notch2 and their ligands Jagged 1 ( Jag1 ) and 2 ( Jag2 ) ( 4850 ), Bmp4 and Bmp7 ( 5153 ), Wnt4 and Wnt7a ( 54, 55 ), and the receptor for hepatocyte growth factor, Met . The lower expression of basal cell-specific markers and essential factors that are needed for differentiation of other cell types like ciliated and goblet cells may explain why the growth of in particular airway organoids was inhibited most by nylon.…”
Section: Resultsmentioning
confidence: 99%
“…Proliferation markers like proliferation marker protein 67 ( Mki67 ), forkhead box protein M1 ( Foxm1 ), and polo-like kinase 1 ( Plk1 , Figure 9E) confirmed this general lack of proliferation in epithelial cells as all three were expressed at lower levels in a dose-dependent manner after exposure to nylon fibers. Expression of genes for signaling molecules essential for epithelial growth and development were impressively and dose-dependently downregulated by nylon exposure as well (Figure 9F), including Notch1 and Notch2 and their ligands Jagged 1 ( Jag1 ) and 2 ( Jag2 ) ( 4850 ), Bmp4 and Bmp7 ( 5153 ), Wnt4 and Wnt7a ( 54, 55 ), and the receptor for hepatocyte growth factor, Met . The lower expression of basal cell-specific markers and essential factors that are needed for differentiation of other cell types like ciliated and goblet cells may explain why the growth of in particular airway organoids was inhibited most by nylon.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative model for use as monolayers for viral infection, we developed hiPSC-derived AT2 cells and alveolospheres (Fig 3C), using established protocols (Huang et al, 2020). Because they were grown in the presence of CHIR99021 (an aminopyrimidine derivate that is a selective and potent Wnt agonist) (Abdelwahab et al, 2019;, which probably inhibits the AT2→AT1 differentiation, these monolayers were enriched for AT2 and devoid of AT1 cells (Fig 3D).…”
Section: Organoid Cellularity Resembles Tissue Sources In 3d Culturesmentioning
confidence: 99%
“…AT2s behave as stem cells and are responsible for regeneration after alveolar epithelium injury. In vitro treatment with several Wnt ligands on AT2-like cells downregulates specific AT2 markers and upregulates AT1 markers, however there are significant differences with influence of particular Wnt ligands in the process [65]. It has been confirmed that also the environment has an influence on the activity of Wnt pathway and then through transcriptional mechanism initiates trans-differentiation [66].…”
Section: Biotechnology Of Stem Cellsmentioning
confidence: 99%